GreenSoftwareLab: towards an engineering discipline for green software - Saraiva, João (2018)
This article summarises the work of a research team focused on reducing energy consumption across various computing systems (mobile, programs, databases, etc.). The team specifically focus on the software side, where our mission is to apply (source code) analysis and transformation techniques to detect anomalies in energy consumption and to define optimizations to reduce such consumption.